Contradictory concepts in tortuosity determination in porous media in electrochemical devices. (20th July 2017) - Tjaden, Bernhard; Finegan, Donal P.; Lane, Jonathan; Brett, Dan J.L.; Shearing, Paul R.
Highlights: Microstructural analysis of oxygen transport membrane porous supports. Correlative tortuosity determinations via X-ray tomography and diffusion cell experiments. Evaluation of the effect of tortuosity, porosity and sample thickness on diffusion resistance. Visible differences between different tortuosity calculation approaches are encountered. Diffusion cell experiments yield the highest and geometric image quantification results in the lowest tortuosity values. Abstract: Porous media are a vital component in almost every electrochemical device in the form of electrode, support or gas diffusion layers. Microstructural parameters of porous layers such as tortuosity, porosity and pore size diameter are of high importance and crucial for diffusive mass transport calculations. Among these parameters, the tortuosity remains ill-defined in the field of electrochemistry, resulting in a wide range of different calculation approaches. Here, we present a systematic approach of calculating the tortuosity of different porous samples using image and diffusion cell experimental-based methods. Image-based analyses include a selection of geometric and flux-based tortuosity calculation algorithms. Differences between the image and diffusion cell-based results are encountered and attributed to the small pore diameters and thereby induced Knudsen effects within the samples which govern the diffusion flux.